Cholesterol Embolism after Cardiac Catheterization: A Case Report and Literature Review - Tiaochoktrakul, Salinthip; Sritippayawan, Suchai; Sitthinamsuwan, Panitta (Journal of the Nephrology Society of Thailand, 2023)
Aging is the major risk factor for atherosclerosis and cardiovascular disease. As aging population increases, more patients develop coronary artery disease requiring diagnostic and therapeutic interventions such as coronary artery angiogram and angioplasty. One of the complications of such procedure is the rupture of cholesterol plaque. The cholesterol emboli can travel to more distal part of the arteries causing obstruction leading to organ ischemia as well as inflammation. If the emboli occludes renal arterial system, acute kidney injury or acute kidney disease may be the results. Patients typically present with progressive decline in renal function in association with ischemia of the skin and/or other organs. Making a diagnosis of cholesterol embolism requires high clinical suspicion in susceptible patients who undergo major cardiovascular procedure.